2010
DOI: 10.1002/pros.21180
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D pathway gene variants and prostate cancer prognosis

Abstract: Background Observational studies linking vitamin D deficiency with increased prostate cancer mortality and the pleiotropic anticancer effects of vitamin D in malignant prostate cell lines have initiated trials examining potential therapeutic benefits of vitamin D metabolites. There have been some successes but efforts have been hindered by risk of inducing hypercalcemia. A limited number of studies have investigated associations between variants in vitamin D pathway genes with aggressive forms of prostate canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 48 publications
3
70
1
1
Order By: Relevance
“…Similarly, vitamin D pathway gene variants may be associated with both disease recurrence/progression and prostate-specific mortality (Holt et al, 2010). Our current study, however, found no evidence that circulating levels or vitamin D genotypes influence postdiagnosis PSA DT in men on active monitoring.…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…Similarly, vitamin D pathway gene variants may be associated with both disease recurrence/progression and prostate-specific mortality (Holt et al, 2010). Our current study, however, found no evidence that circulating levels or vitamin D genotypes influence postdiagnosis PSA DT in men on active monitoring.…”
Section: Resultscontrasting
confidence: 75%
“…Vitamin D levels may be associated with the risk of disease progression (Chen et al, 2009;Holt et al, 2010) and the risk of progression may potentially be lowered by increasing a man's circulating vitamin D level (Gross et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological evidence also link low serum levels of vitamin D metabolites and the expression of genetic variants within its hormonal pathway with increased risk of prostate cancer, its recurrence/progression and cancer-specific mortality (Schwartz and Hulka, 1990;Huang et al, 2006;Xu et al, 2003;Williams et al, 2004;Holt et al, 2010). In addition, the hormonally active form of vitamin D that is 1,25(OH) 2 D 3 (henceforth referred to as 1,25D) exerts well documented growth-regulatory effects upon prostate cancer cell lines that includes regulated expression of the cell cycle-related genes p21( waf/cip1 ) and p27( kip1 ) in addition to interference with growth factor signaling through induction of the IGFBP3 gene (Sinkkonen et al, 2005;Wu et al, 1997;Peng et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…In our association study, we evaluated a novel VDR polymorphism detectable with Dde I restriction enzyme, which have reported a significant association in the prostate cancer [34]. However, it seems the Dde I polymorphism is not a candidate genetic marker for urinary stone disease.…”
Section: Commentmentioning
confidence: 97%